Illness perception and related behaviour in lower respiratory tract infections—a European study. (18th November 2014) - Hordijk, Patricia M; Broekhuizen, Berna D L; Butler, Chris C; Coenen, Samuel; Godycki-Cwirko, Maciek; Goossens, Herman; Hood, Kerry; Smith, Richard; van Vugt, Saskia F; Little, Paul; Verheij, Theo J M
Abstract: Background: Lower respiratory tract infection (LRTI) is a common presentation in primary care, but little is known about associated patients' illness perception and related behaviour. Objective: To describe illness perceptions and related behaviour in patients with LRTI visiting their general practitioner (GP) and identify differences between European regions and types of health care system. Methods: Adult patients presenting with acute cough were included. GPs recorded co morbidities and clinical findings. Patients filled out a diary for up to 4 weeks on their symptoms, illness perception and related behaviour. The chi-square test was used to compare proportions between groups and the Mann-Whitney U or Kruskal Wallis tests were used to compare means. Results: Three thousand one hundred six patients from 12 European countries were included. Eighty-one per cent ( n = 2530) of the patients completed the diary. Patients were feeling unwell for a mean of 9 (SD 8) days prior to consulting. More than half experienced impairment of normal or social activities for at least 1 week and were absent from work/school for a mean of 4 (SD 5) days. On average patients felt recovered 2 weeks after visiting their GP, but 21% ( n = 539) of the patients did not feel recovered after 4 weeks. Twenty-seven per cent ( n = 691) reported feeling anxious or depressed, and 28% ( n = 702) re-consulted their GP at some point during the illness episode. Reported illness duration and days absent from work/school differed between countries and regions (North-West versus South-East), but there was little difference in reported illness course and related behaviour between health care systems (direct access versus gate-keeping). Conclusion: Illness course, perception and related behaviour in LRTI differ considerably between countries. These finding should be taken into account when developing International guidelines for LRTI and interventions for setting realistic expectations about illness course.